Industrial clusters: The case for Special Economic Zones in Africa - Carol Newman; John M. Page (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Firms tend to cluster in close geographic proximity to each other to benefit from reduced transport costs, shared inputs, and productivity spillovers due to learning and technology transfers. Evidence from low-income countries suggests that such agglomeration economies may be substantial in endogenously formed clusters. This raises the question of whether spatial industrial policies can be designed to facilitate clustering. In this paper, we consider the case for creating Special Economic Zones (SEZs) in Africa. We document at the country level the state of current SEZ programmes and the policy measures in place for their promotion. We give an overview of the evidence on their success and provide a set of policy recommendations to improve SEZs performance.
Keywords: O14; O25; 330; agglomeration; Special Economic Zones; spatial industrial policy; Africa